THE SOCIAL JUSTICE IMPLICATIONS OF THE US DRUG WAR - Robinson, Matthew; Jones, Maggie; Jones, Maggie (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2015)
In this paper, the authors outline key facts pertaining to the US drug war, including its stated goals and objectives, and then offer an assessment of the empirical evidence related to its (in)effectiveness in achieving these goals. Data illustrate that drug use is not down, that availability of drugs is not down, that the price of drugs is not down, that access to drug treatment has not increased, and that deaths and illnesses associated with drugs use are not down. The authors also identify major costs associated with national drug control policy and weigh these against its benefits. This analysis permits a conclusion with regard to whether the drug war is a good or bad policy. Finally, the authors utilize major theories of justice to identify whether the drug war is consistent with social justice. The analysis shows that the drug war does not commonly accepted definitions of social justice.